(untitled) (Communications in Mathematical Research, 2022)
This paper presents a formula for the Drazin inverses of matrices based on a sequence of partial full-rank factorizations which theoretically extends the classic full-rank factorization method for computing the Drazin inverses established by R.E. Cline. The result is then extended to the core-EP inverses.